ANALISIS USAHA BUDIDAYA IKAN DALAM KERAMBA DI DESA REBAQ RINDING KECAMATAN MUARA MUNTAI KABUPATEN KUTAI KARTANEGARA - fahri iswanto; Heru Susilo; Oon Darmansyah (Jurnal Pembangunan Perikanan dan Agribisnis, 2024)
The of this study are to determine the cost, revenue, income and revenue cost rasio. This study was carried out from august 2021 to september 2021. The sample taken was 36 respondents consisting of 2 commodities, common carp and tilapia. The sampling method used is census. The data analysis method used is income analysis and revenue cost rasio. The results showed that the profit from the fish farming business in cages in Rebaq Rinding Village averaged Rp. 2.875.714/Harvest for common carp dan tilapia averaged Rp. 1.585.912/Harvest. The ratio value of fish farming businesses in cages in Rebaq Rinding Village averages 1,5. Keywords : common carp and Tilapia, Cage, Rebaq Rinding Village